Big Data Warehouse Architecture for ensuring Privacy - Ansari Aadil Salim, Faizan Ahmed, Abdullah Nasir Khan, Sana Irfan Ahmad Asjad Kamal (International Journal of Advanced Science and Technology, 2020)
Big Data is a collection of data that is big or Hugh in size and yet increasing exponentially with time. This type of data is so large and made of heterogeneous type of information that none of the traditional data management tools are able to process it efficiently and store it. Along with the ever increasing growth in data collection and its mining, there is an increasing threat of compromising population and individual privacy. Many techniques have been proposed in literature to preserve privacy of integrated data while storing and processing. In this paper, we propose a privacy-ensuring architecture for processing and storing data in a big data warehouse. Especially, we propose a pliable, extendable, and adaptable architecture in the form of Embedded Privacy Agreements which compel user specified privacy requirements. In this paper we discuss the implementation details of system architecture.